The Impact of the Implementation of Sharia Accounting on Company Values Along with the Development of Sharia Accounting in Indonesia - Irsad Rukman (Takaza Innovatix Labs Ltd., 2024)
This study discusses the growing relevance of Sharia accounting in Indonesia’s economic environment, which emphasizes Islamic principles prohibiting usury, uncertainty, and gambling. The research aims to analyze the impact of Sharia accounting implementation on firm value within the context of its regulatory and institutional development in Indonesia. A qualitative approach with library research was employed, using a purposive sample of 20–30 sources published between 2021 and 2025 from Sinta, Scopus, and Google Scholar databases. Data were collected from books, journals, and institutional documents, analyzed through thematic synthesis and triangulation techniques to ensure data validity. The findings reveal that the implementation of Sharia accounting enhances firm value through improved stakeholder trust, better transparency, and access to Sharia-compliant markets. The conclusion underscores that consistent application, human resource capacity building, and technological adaptation are essential to overcome regulatory challenges and ensure sustainable Sharia-based business practices.